A rise-assisting robot extends life space and improves facial expressions of nursing home residents - Kenji Kato; Tatsuya Yoshimi; Keita Aimoto; Kenji Sato; Naoki Itoh; Izumi Kondo (BMC Health Services Research, 2022)
Abstract Background The introduction of nursing care-support devices using robotic technology is expected to reduce the task burden in long-term care facilities. Objective To investigate the use of the rise-assisting robot, Resyone, in extending and improving the life space of nursing home residents with severe care needs. Methods We performed a feasibility study in which Resyone was used to facilitate visits to additional sites in and around the nursing home as part of the care package of three residents. Two weeks before and four weeks after implementation of the new arrangements, the 30 caregivers involved were asked to record transfer times and destinations, while also checking the residents’ facial expressions. Results Before implementation, participants had limited life spaces, but afterwards they regularly visited additional destinations including the garden, home entrance and corridors, which previously they had not visited frequently. The residents' facial expressions became more positive and less negative. This study demonstrates that Resyone can enrich care activities in severely disabled individuals. Conclusion These findings suggest that the sustainable use of Resyone would improve the quality of care at care facilities. Moreover, the extension of otherwise limited life space has the potential to improve care receivers’ quality of life. Trial registration UMIN Clinical Trials Registry No. UMIN000039204 (20/01/2020); retrospectively registered; interventional study; parallel, non-randomized, single blinded. URL of trial registry records: https://upload.umin.ac.jp/cgi-open-bin/ctr_e/ctr_view.cgi?recptno=R000044709 .